Long-Term Outcome of Gamma Knife Radiosurgery for Vestibular Schwannoma - Bir, Shyamal C.; Ambekar, Sudheer; Bollam, Papireddy; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective We evaluated the long-term outcome of vestibular schwannoma (VS) treated with gamma knife radiosurgery (GKRS) as a primary treatment as well as an adjunct therapy.Materials and Methods We performed a retrospective review (2000–2012) of 82 patients with VS who received GKRS. Of 82 patients, 20 patients with prior resection received GKRS treatment as an adjunct therapy. The remainder of the patients (62) received GKRS as a primary treatment.Results GKRS for VS showed significant variations in tumor growth control (decreased in 44 patients [54%], arrested growth in 30 patients [36%], and increased tumor size in 8 patients [10%]). Progression-free survival rates after GKRS at 3, 5, and 10 years were 98%, 95%, and 95%, respectively. Hearing, facial nerve function, and Karnofsky performance scale were significantly improved after GKRS compared with pretreated status (79 versus 90). Two patients (2.5%) required resection again due to tumor progression and worsening of signs and symptoms.Conclusion Long-term follow-up demonstrated that GKRS offers a high rate of tumor control, preservation of multiple nerve functions, and a good quality of life in both new and recurrent patients with VS.
Keywords: vestibular schwannoma; gamma knife radiosurgery; long-term outcome